2020
DOI: 10.3390/ijerph17031032
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Particulate Matter Levels during 2017 Large Forest Fires and Megafires in the Center Region of Portugal: A Public Health Concern?

Abstract: This work characterizes the dimension and the exceptionality of 2017 large- and mega-fires that occurred in the center region of Portugal through the assessment of their impact on the ambient levels of particulate matter (PM10 and PM2.5), retrieved from local monitoring stations, and the associated public health risks. PM10 and PM2.5 concentrations were increased during the occurrence of large fires and megafires, with daily concentrations exceeding the European/national guidelines in 7–14 and 1–12 days of 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 55 publications
1
34
0
2
Order By: Relevance
“…Thirty papers reported on elements of adverse health outcomes related to bushfire smoke exposure. Fifteen articles described community medical/health seeking behaviour during bushfire smoke events [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. Nine articles documented mortality statistics during these events [51][52][53][54]58,59,[63][64][65].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty papers reported on elements of adverse health outcomes related to bushfire smoke exposure. Fifteen articles described community medical/health seeking behaviour during bushfire smoke events [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. Nine articles documented mortality statistics during these events [51][52][53][54]58,59,[63][64][65].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen articles described community medical/health seeking behaviour during bushfire smoke events [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. Nine articles documented mortality statistics during these events [51][52][53][54]58,59,[63][64][65]. Twelve articles outlined morbidity data [49][50][51][52][53][54]57,58,61,62,66,67].…”
Section: Resultsmentioning
confidence: 99%
“…The estimated emission of PM 2.5 (Ø < 2.5 µm) from wildland fires is 0.9-16 g for each kg of burned dry biomass [10]. In South Europe as well as in South America, it was demonstrated that the release of PM by wildland fires, can significantly contribute to the airborne PM levels causing the exceeding of air quality standards [5,[14][15][16]. These standards are set for PM regardless of its origin; however, the composition of wildland fire PM may be different from urban PM.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the most concerning aspect that is related to wildfires is the adverse public health effect that is caused by the exposure to biomass burning emissions, which causes every year hundreds of thousands of deaths worldwide (i.e., 339,000 people annually, estimated for the period 1997-2006 by [4]). Indeed, the main compounds emitted by wildfires, including aerosol (i.e., fine and coarse particulate matter, PM) and trace gases, such as carbon monoxide (CO), methane (CH 4 ), nitrous oxide (N 2 O), nitrogen oxides (NOx), and volatile organic carbon (VOC) [5], appeared to have an adverse effect on all-cause mortality and respiratory morbidities, like asthma, chronic obstructive pulmonary disease (COPD), bronchitis, and pneumonia [6][7][8]. This global public health issue is growing, particularly in areas where large and widespread wildfires are becoming an increasing concern [2,9].…”
Section: Introductionmentioning
confidence: 99%
“…SD can easily reach the Mediterranean countries [12], but it can also be transported and distributed across the planet [13] with different frequencies of occurrence and with consequent influence on PM concentration levels, depending, among many factors, on the proximity of the source areas [12,14]. While the SD episodes worldwide are rare and of low intensity [14,15], they are frequently recorded in European Mediterranean countries, strongly affecting PM concentrations [8,12,[16][17][18][19][20]. Many studies observed that SD events often cause the exceedance of the PM 10 limits [12] that were established by the European Air Quality Directive (EU 2008/50/EC).…”
Section: Introductionmentioning
confidence: 99%